2019
DOI: 10.3389/fcimb.2019.00429
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Exposure to Fusobacterium nucleatum Triggers Chemokine/Cytokine Release and Inhibits the Proliferation and Osteogenic Differentiation Capabilities of Human Gingiva-Derived Mesenchymal Stem Cells

Abstract: Fusobacterium nucleatum is one of the most frequent pathogenic bacteria causing periodontitis. The direct effect of Fusobacterium nucleatum (F. nucleatum) on oral stem cells has rarely been reported. In this study, we aimed to evaluate how gingiva-derived mesenchymal stem cells (GMSCs) respond to a direct challenge with F. nucleatum. GMSCs were isolated by the limiting dilution method and exposed to F. nucleatum at various multiplicities of infection (MOIs; F. nucleatum:cell ratios of 10:1, 50:1, and 100:1) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
(65 reference statements)
2
22
0
Order By: Relevance
“…The mRNA expression profile of GSE126821 in the GEO database 1 has been reanalyzed, which has been deposited according to our previous study (Kang et al, 2019). Briefly, three healthy individuals who underwent impacted tooth extraction at Stomatology Hospital of Shandong Province were recruited to participate in this study.…”
Section: Microarray Datamentioning
confidence: 99%
“…The mRNA expression profile of GSE126821 in the GEO database 1 has been reanalyzed, which has been deposited according to our previous study (Kang et al, 2019). Briefly, three healthy individuals who underwent impacted tooth extraction at Stomatology Hospital of Shandong Province were recruited to participate in this study.…”
Section: Microarray Datamentioning
confidence: 99%
“…Upregulation of CCL20 and CSF-3 (G-CSF) has been shown in Fn-infected esophageal tumor tissue and gingival fibroblasts, respectively (Kang et al, 2019a;Yamamura et al, 2016). CSF-2 (GM-CSF) upregulation has been observed in Fn-infected gingiva-derived mesenchymal stem cells (Kang et al, 2019b), and a role for CSF-2 in CRC epithelial-mesenchymal transition has been proposed (Chen et al, 2017). We show upregulation of CCL20, CSF-3, and CSF-2 is induced in both HCE and HCAE cells upon exposure to all Fn strains tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of bacteria on GMSCs, Kang W et al found that persistent exposure to F. nucleatum promotes cell migration and chemokine/cytokine release but suppresses the proliferation and osteogenic differentiation of GMSCs (148). In vivo, Su Y et al reported that altered oral microbiome and an increased LPS level caused by antibiotic treatment led to GMSCs deficiency and proliferation inhibition and a delayed wound healing in mice (122).…”
Section: Effects Of Infection/inflammation On Gmscsmentioning
confidence: 99%